Post-obduction slab dynamics in the Balkans and its role in Late Cretaceous magmatism: A numerical modelling approach - Stanković, Nikola; Cvetković, Vladica; Mladenović, Ana; Cvetkov, Vesna; Prelević, Dejan; Gerya, Taras (Gondwana research, 2026)
[Display omitted] •Post-obduction slab dynamics can account for post-collisional magmatism.•Timok Magmatic Complex does not require active subduction and an open ocean.•Numerical magmatic-thermomechanical modelling recreates westward magma progression.•Slab break-off is a viable mechanism for post-collisional porphyry mineralization. The geodynamic evolution of the Balkan Peninsula during the Late Cretaceous remains a subject of debate, particularly regarding the role of subduction versus post-collisional processes for magmatism. This study employs magmatic-thermomechanical numerical modelling to investigate the fate of the Upper Jurassic subducted Adriatic lithosphere following the compressional obduction processes related to the emplacement of the Tethyan ophiolites onto the Adriatic margin. Our results suggest that Late Cretaceous magmatism in the Timok Magmatic Complex can be explained without invoking the existence of an actively subducting oceanic domain (e.g. “Sava Ocean”). Instead, the magmatic activity appears to be a consequence of slab breakoff, lithospheric delamination, and the subsequent rebound of subducted continental material. The model successfully reproduces key geological observations, including the delayed onset of magmatism (relative to the Late Jurassic closure of Vardar Tethys) and the geochemical signatures typically associated with subduction. However, discrepancies remain in the precise timing of volcanism, which highlights the need for further refinements in numerical modelling of melt extraction and magma migration processes. These findings contribute to a broader general understanding of post-obduction geodynamic processes and have implications for the formation of porphyry Cu-Au deposits in post-collisional settings.